IMPLEMENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI DIGITAL STORYTELLING PADA PESERTA DIDIK DI TADIKA AL-FIKH ORCHARD, BANDAR PARKLAND SELANGOR MALAYSIA - Zidan Azbial Farruq Siregar; Rahimah Rahimah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study was motivated by the limited research on the implementation of Islamic religious education values based on technology, particularly Digital Storytelling. This study aims to describe and analyze the implementation of Islamic Religious Education (IRE) values Islamic Religious Education (IRE) through digital storytelling among students at Tadika Al-Fikh Orchard, Bandar Parkland, Selangor, Malaysia. The main issue examined is how digital story-based media is used as a means of instilling Islamic values in early childhood amid the challenges of the digital age. This study uses a qualitative approach with a descriptive design . Data was collected through direct observation of learning activities, in-depth interviews with teachers and the head of the kindergarten, as well as documentation in the form of videos, digital teaching materials, and student work. Data analysis was conducted using Miles and Huberman's interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of digital storytelling was carried out in a planned manner through the stages of planning Islamic themes, selecting digital media (animated videos, illustrations, nasyid), and reflective activities that reinforce the values of faith, worship, morals, and social values. Students showed positive responses in the form of enthusiasm, increased understanding of Islamic values, and changes in religious and social behavior. This study confirms that digital storytelling can be an effective learning strategy for shaping the Islamic character of early childhood with the support of technology, teacher creativity, and parent collaboration. The implication is that PAI learning needs to be directed towards a humanistic and inspiring digital media-based contextual approach.